A Tale of Winglets: Evolution of Flight Morphology in Stick Insects - Zeng, Yu; O'Malley, Connor; Singhal, Sonal; Rahim, Faszly; Park, Sehoon; Chen, Xin; Dudley, Robert (Frontiers in Ecology and Evolution, 2020)
The evolutionary transition between winglessness and a full-winged morphology requires selective advantage for intermediate forms. Conversely, repeated secondary wing reductions among the pterygotes indicates relaxation of such selection. However, evolutionary trajectories of such transitions are not well-characterized. The stick insects (Phasmatodea) exhibit diverse wing sizes at both interspecific and intersexual levels, and thus provide a system for examining how selection on flight capability, along with other selective forces, drives the evolution of flight-related morphology. Here, we examine variation in relevant morphology for stick insects using data from 1,100+ individuals representing 765 species. Although wing size varies along a continuous spectrum, taxa with either long or miniaturized wings are the most common, whereas those with intermediate-sized wings are relatively rare. In a morphological space defined by wing and body size, the aerodynamically relevant parameter termed wing loading (the average pressure exerted on the air by the wings) varies according to sex-specific scaling laws; volant but also flightless forms are the most common outcomes in both sexes. Using phylogenetically-informed analyses, we show that relative wing size and body size are inversely correlated in long-winged insects regardless of sexual differences in morphology and ecology. These results demonstrate the diversity of flight-related morphology in stick insects, and also provide a general framework for addressing evolutionary coupling between wing and body dimensions. We also find indirect evidence for a “fitness valley” associated with intermediate-sized wings, suggesting relatively rapid evolutionary transitions between wingless and volant forms.